Study and Comparison Between Personality Traits and Coping Strategies Among Opium Addicts (within the age of 30-36) - Alireza Jazayeri; Zabihollah Jafarizadeh; Abbas Pourshahbaz (Drug Control Headquarters, Research and Education Office, 2003)
The research is looking into the study and comparison between personality traits and coping strategies and their relationship with one another among opium addicts within the age of 30-36. For this purpose, a research group comprising 50 opium addicts was selected with respect to control variables. In order to compare the results, 50 other individuals were selected as a observation group and with regard to control variables both groups were matched together. The five-factor personality trait inventory (NEO-FFI) and the coping strategy inventory of Carver and Shearer were used. Moreover, in order to control the effects of depression and anxiety on personality traits, Beck's test for anxiety and depression was used. The results indicated that without taking the effects of depression and anxiety into account, the addicts showed higher neuroticism trait but lower extraversion, agreeableness and conscientious traits. But when the effects of depression and anxiety were taken into account, the two groups showed a meaningful difference in the conscientious trait. Furthermore, addicts rarely use concentrated coping strategies and usually use non-effective strategies. Non-effective strategies had direct relationship with neuroticism and opposite relationship with conscientiousness.